Fracture analysis of perpendicular to grain loaded dowel-type connections using a 3D cohesive zone model. Issue 5 (19th October 2016) - Danielsson, Henrik; Gustafsson, Per Johan
Abstract: The strength and fracture behavior of dowel-type connections with stiff dowels loaded perpendicular to grain was studied by nonlinear 3D finite element (FE)-analysis. A cohesive zone model was used to model the perpendicular to grain fracture of the wood, i.e., failure by wood splitting along the grain. The influence of load eccentricity and dowel-to-loaded-edge distance was studied for a plate type of geometry loaded in tension and for a simply supported beam loaded in bending. The strength found from the FE-analysis is compared to strength from experimental tests with centric loading, showing overall good agreement. Numerical results for centric loading are further compared to strength predictions according to the linear elastic fracture mechanics (LEFM)-based design criterion present in Eurocode 5 (EN 1995-1-1:2004). The comparison showed good agreement regarding the relative influence of connection geometry, but the design criterion appears, however, to yield unconservative strength predictions. The results of the FE-analyses regarding dowel load eccentricity showed that such loading conditions may yield significantly lower strengths compared to centric loading. An approximate engineering method to account for the strength reduction due to load eccentricity is, furthermore, presented.